Integrated life-cycle assessment and thermal dynamic simulation of alternative scenarios for the roof retrofit of a house - Rodrigues, Carla (2014)
Building retrofit plays an important role in reducing environmental loads associated with the building stock. The main goal of this article is to perform a comprehensive energy and environmental life-cycle assessment (LCA) of the roof retrofit of a Portuguese single-family house integrating thermal dynamic simulation. A life-cycle model was developed to assess 27 alternative retrofit scenarios combining three types of insulation material (rock wool, extruded polystyrene and polyurethane foam), three insulation levels (40, 80 and 120 mm) and three types of frame material (wood, light steel and lightweight concrete). The functional unit selected for this study was 1 square meter of living area over a period of 50 years. Life-cycle (LC) impact assessment results were calculated for six categories showing that wood scenarios had the lowest impacts (all categories). The use phase accounted for 60–70% of the LC impacts in all categories. The results also showed that for insulation thicknesses of 80 mm or more, the reduction in operational energy, due to a further increase of 40 mm, is not significant (5% or less), while the embodied impacts increase from 6 to 20%. This article shows the importance of addressing the entire life-cycle of building retrofit to reduce environmental impacts by quantifying the marginal LC benefit of additional insulation levels and provides recommendations for optimal insulation levels for Mediterranean climates.